A Study of Mathematics Learning Outcomes and Creativity of Ninth Graders Using STEM Education - ภูมิโคกรักษ์ ศิวณัฐ; กิตติสุนทร เจษฎา (Ratchaphruek Journal, 2019)
The purposes of this thesis were 1) to study of Mathematics learning outcomes and creativity for ninth grade using STEM education were; 1.1) to compare Mathematics achievement of ninth graders before and after using STEM education, 1.2) to compare Mathematics achievement of ninth graders after using STEM education with 70% criterion, 1.3) to study task performance of ninth graders after learning using STEM education, and 2) to compare the creativity of ninth graders before and after using STEM education. The samples were 25 ninth graders of Pimaidamrong Wittayakom School under secondary educational service area office 31, who studying in the second semester of academic year 2017. The sample group was selected using cluster random sampling. Research instruments consisted of 3 STEM lesson plans, achievement test, task performance evaluation form, and creativity assessment forms. Data analysis was carried out with the use of average, percentage, standard deviation and t-test. The study revealed that: 1) Mathematics achievement of ninth graders after using STEM education was higher significantly than before at the .05 level. 2) Mathematics achievement of ninth graders after using STEM education was not higher than 70% criterion at the .05 level. 3) Task performance of ninth graders after using STEM education was very good. 4) Creativity of ninth graders after using STEM education was higher significantly than before at the .05 level.